Outcomes of Gonioscopy-assisted Transluminal Trabeculotomy (GATT) in Eyes With Prior Incisional Glaucoma Surgery. Issue 1 (January 2017) - Grover, Davinder S.; Godfrey, David G.; Smith, Oluwatosin; Shi, Wei; Feuer, William J.; Fellman, Ronald L.
Abstract : Purpose: To report on outcomes of gonioscopy-assisted transluminal trabeculotomy (GATT) in eyes with prior incisional glaucoma surgery. Patients and Methods: A retrospective review was performed for all patients who underwent a GATT procedure with a history of prior incisional glaucoma surgery. Results: Thirty-five eyes of 35 patients were treated. The mean age was 67.7 years. Nineteen eyes had a prior trabeculectomy, 13 eyes had a prior glaucoma drainage device, 4 eyes had a prior trabectome, and 5 eyes had prior endocyclophotocoagulation. Mean follow-up time was 22.7 months. For all eyes, the mean preoperative intraocular pressure (IOP) (SD) was 25.7 (6.5) mm Hg on 3.2 (1.0) glaucoma medications and at 24 months, the mean IOP (SD) was 15.4 (4.9) mm Hg on 2.0 (1.4) glaucoma medications ( P <0.001). The prior trabeculectomy group had a preoperative IOP (SD) of 24.6 (6.4) mm Hg on 3.2 (1.0) medications and at month 24, the mean IOP (SD) was 16.7 (5.6) mm Hg on 2.1 (1.4) glaucoma medications. In the prior glaucoma drainage device group, the mean preoperative IOP (SD) was 27.0 (7.1) mm Hg on 3.4 (1.1) glaucoma medications and at 24 months, the mean IOP (SD) was 12.9 (2.6) mm Hg on 2.1 (1.2) glaucoma medications. At 24 months, the cumulative proportion of failure was 0.4 and the cumulative proportion of reoperation was 0.29. Conclusions: GATT appears to be safe and successful in treating 60% to 70% of open-angle patients with prior incisional glaucoma surgery. When considering all eyes, there was a significant decrease in IOP and required glaucoma medications at 24 months. This surgery should be considered in certain patients with open angles who have failed a primary traditional glaucoma surgery.